2002
DOI: 10.1161/01.res.0000016164.02525.b4
|View full text |Cite
|
Sign up to set email alerts
|

CD36 Mediates the Cardiovascular Action of Growth Hormone-Releasing Peptides in the Heart

Abstract: Abstract-Growth hormone-releasing peptides (GHRPs) are known as potent growth hormone secretagogues whose actions are mediated by the ghrelin receptor, a G protein-coupled receptor cloned from pituitary libraries. Hexarelin, a hexapeptide of the GHRP family, has reported cardiovascular activity. To identify the molecular target mediating this activity, rat cardiac membranes were labeled with a radioactive photoactivatable derivative of hexarelin and purified using lectin affinity chromatography and preparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0
12

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(118 citation statements)
references
References 35 publications
1
105
0
12
Order By: Relevance
“…Cross-linking experiments using hearts from CD36 KO mice showed no binding partner. In an isolated perfused heart system, hexarelin induced a dose dependent vasoconstriction that again was not observed in hearts from CD36 KO mice and spontaneous hypertensive rats (SHR), which have also been shown to lack CD36 (Bodart, et al, 2002). Detailed mapping by enzymatic and chemical degradation showed that the binding site for hexarelin overlapped with the oxLDL site and the apparent point of contact was methionine 169 (Demers, et al, 2004).…”
Section: Cd36 Ligands and Functionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Cross-linking experiments using hearts from CD36 KO mice showed no binding partner. In an isolated perfused heart system, hexarelin induced a dose dependent vasoconstriction that again was not observed in hearts from CD36 KO mice and spontaneous hypertensive rats (SHR), which have also been shown to lack CD36 (Bodart, et al, 2002). Detailed mapping by enzymatic and chemical degradation showed that the binding site for hexarelin overlapped with the oxLDL site and the apparent point of contact was methionine 169 (Demers, et al, 2004).…”
Section: Cd36 Ligands and Functionsmentioning
confidence: 97%
“…Another ligand for CD36 is the GHRP, hexarelin, and a derivative with no growth hormone releasing properties, EP 80317 (Bodart, et al, 2002). Previous work had shown that hexarelin pretreatment of growth hormone deficient rats protected against cardiac damage in ischemia/ reperfusion models.…”
Section: Cd36 Ligands and Functionsmentioning
confidence: 99%
“…Following electrophoresis in 10% Tris-HCl SDS-PAGE gels the separated proteins were transferred onto a PVDF membrane. Membranes were blocked with TBS-Tween containing 5% milk and then incubated with primary polyclonal rabbit antibodies to CD36 (1:5000) [11], followed by donkey anti-rabbit secondary antibody and development with enhanced chemiluminescence (Amersham). Bands were quantified using commercially available software.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Cette enzyme aurait donc pu être impliquée dans les mécanismes de désacylation de la ghréline : il ne semble pas que ce soit le cas [11]. L'hexaréline, mais pas le MK 0677 ni la ghréline, se fixe avec une affinité raisonnable au CD36, un récepteur d'épuration multifonctionnel [12]. Enfin, le (ou les) récepteur(s) relayant les effets de la ghréline non acylée reste(ent) totalement inconnus……”
Section: Combien De Ligands Et De Récepteurs ?unclassified
“…Le CD36 est un récepteur d'épuration multifonctionnel de type B, impliqué dans l'athérogenèse et le métabolisme des lipoprotéines. Exprimé principalement par les cardiomyocytes et les cellules endothéliales de la microvasculature, le CD36 semble intervenir dans les effets cardiovasculaires sélectifs des GHS de nature peptidique [12]. Des effets de la ghréline ont également été décrits sur l'axe reproducteur (la ghréline inhibe l'activité prolifé-rative des cellules de Leydig immatures), sur les systè-mes immunitaires et ostéo-articulaires, ou encore sur le sommeil et l'anxiété [35].…”
Section: Effets Cardiovasculairesunclassified